Volunteer Fire Brigade (OSP) Firefighting Sports Competitions in the Context of Key Problems of Contemporary Rural Poland - Konrad Burdyka (Jan Długosz University in Częstochowa, 2023)
Volunteer Fire Brigades (OSPs) are the most numerous and widespread category of rural non-governmental organisations in Poland. The emergency rescue focus of their activity is conducive to undertaking initiatives in the field of sports, i.e. projects aiming to improve the physical fitness and technical skills of volunteer firefighters. Firefighting sports competitions are the main form of sports rivalry among firefighters. Due to the fact of their long-time and regular organisation, team character, complying with a set of strict rules and rituals, and also the fact that this is rivalry between teams representing local communities that neighbour one another, they are a social and cultural phenomenon in which the problems of today's rural Poland come into focus. Based on field research completed just before the COVID-19 pandemic and an overview of the literature, the author sets out to identify the functions of firefighting sports competitions in local systems. Considering the scale of the OSP organisation and the fact that it is permanently rooted in rural Poland, the paper may be considered a contribution to the discussion on effective ways of promoting physical culture outside urban centres.